MIDDLE CLASS FORMING IN THE UKRAINIAN SOCIETY IN CONDITIONS OF TRANSFORMATION - Довбня, О.М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 2015)
The problems of stratification, polarization and marginality in the Ukrainian society are investigated in the article. In the context of vagueness of the position of certain layers in society stratification, the social base of parties and adequacy of representative office of interests of social layers is estimated in the party programs. The conditions are investigated and the ways of forming middle class in agrarian sector are proposed. It is shown in the article, that small in numbers middle class don’t conduce to the stability of the state, activation population, forming of civil society.